A Scottish university prescribing team's experiences and reflections during the COVID-19 pandemic. (2nd October 2022) - Bell, Suzanne; Coulson, Arlene; Donnelly, Stacey; Henderson, Colette; Hodgson, Alison; Rolfe, Sandy
Abstract: The onset of the pandemic and associated restrictions led to the closure of university buildings across Scotland in March 2020. This was immediately followed by the introduction and embedding of online learning, teaching and assessment from previous class or blended delivery modules across all curricula. Academics were required to structure and develop quality student materials from their own homes. In addition, approved programmes of study, such as the prescribing module, had to ensure governance and teaching and learning aligned to Professional Statutory and Regulatory Bodies requirements for students and staff now working and studying at home. There was a recognition that NHS stakeholders and clinical practitioners required support with continuing professional education incorporating robust awareness of critical practice needs and the safety of patients and staff in clinical areas.